(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the present study, security is considered a category related to the protection of the national sovereignty and interests of the country. Today, we live in an international environment, and politics and security are closely intertwined. The law of international relations regulates relations between states and defines their rights and obligations in many areas, including trade, environmental protection, human rights, and peaceful coexistence. The principle of sovereignty is one of the most fundamental principles of international law. Therefore, each country is entitled to govern its territory and people without interference from other countries. The paper discusses how international law and sovereignty contribute to maintaining international order, security, and cooperation. International law not only provides a framework for resolving conflicts between states but also mechanisms for promoting international cooperation on a broad range of issues. It also provides a framework for the peaceful settlement of conflicts and protects vulnerable groups such as refugees and displaced persons. Are you aware of the contemporary challenges that threaten to protect our country’s sovereignty? It’s a crucial issue that needs our attention. Let’s understand the challenges we face in protecting our nation’s sovereignty.